The Effect of Green Human Resource Management on Green Service Behavior Mediated by Corporate Social Responsibility - Setiyani, Shinta Dwi; Wening, Nur (Manunggal Halim Jaya, 2025)
This study aims to analyze the influence of green human resource management on green service behavior mediated by corporate social responsibility at PT X. The study uses green service behavior variable indicators, namely extra-role green service and intra-role green service. The method used in sampling is nonprobability sampling of 127 respondents. Primary data collection using a questionnaire method. This study uses validity, reliability, normality, heteroscedasticity, linearity, simple linear regression analysis, t-test, coefficient of determination test, path analysis, and path coefficient. The results of the study showed that: (1) Green human resource management has a significant positive effect on extra-role green service. (2) Green human resource management has a significant positive effect on intra-role green service. (3) Green human resource management has a significant positive effect on corporate social responsibility. (4) Corporate social responsibility does not have a significant positive effect on extra-role green service. (5) Corporate social responsibility has a significant positive effect on intra-role green service. (6) Green human resource management and corporate social responsibility have a simultaneous influence on extra-role green service. (7) Green human resource management and corporate social responsibility have a simultaneous influence on intra-role green service.